1992
DOI: 10.1002/1097-0142(19920115)69:2<346::aid-cncr2820690212>3.0.co;2-e
|View full text |Cite
|
Sign up to set email alerts
|

Internal radiation therapy for hepatocellular carcinoma. Results of a french multicenter phase II trial of transarterial injection of iodine 131-labeled lipiodol

Abstract: Preliminary Phase I trials have shown iodine 131 (131I)‐Lipiodol (ethiodized oil; Laboratoires Guerbet, Aulnay‐sous‐Bois, France) to be well tolerated and most likely effective in the treatment of hepatocellular carcinoma (HCC). In this multicenter Phase II trial, the authors tested the feasibility and reproducibility of this treatment in other medical institutions and evaluated its efficacy in 50 patients with unresectable Stage I or II HCC, by the classification of Okuda et al. The authors studied 47 men and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

1994
1994
2012
2012

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(19 citation statements)
references
References 14 publications
1
18
0
Order By: Relevance
“…1, the mean absorbed dose for the most relevant organs was comparable between the MCNP calculations and MIRDOSE. Our result for the normal liver is comparable to the absorbed liver dose calculated by Raoul et al [14] (5.5 Gy, SD 8.7), although their absorbed dose to the lungs was lower, with a maximum of 2.9 Gy (SD 2.2). Direct effects after therapy were never observed even though some of our patients were treated with 131 I-lipiodol up to 5 times.…”
Section: Discussionsupporting
confidence: 88%
“…1, the mean absorbed dose for the most relevant organs was comparable between the MCNP calculations and MIRDOSE. Our result for the normal liver is comparable to the absorbed liver dose calculated by Raoul et al [14] (5.5 Gy, SD 8.7), although their absorbed dose to the lungs was lower, with a maximum of 2.9 Gy (SD 2.2). Direct effects after therapy were never observed even though some of our patients were treated with 131 I-lipiodol up to 5 times.…”
Section: Discussionsupporting
confidence: 88%
“…30 These findings indicate that I-131-Lip has potential advantages for use in hepatoma therapy. [31][32][33] The selective delivery and retention of lipiodol are thought to result from the developed neovasculature, enhanced permeability and the poor reticuloendothelial systems observed in hepatoma tissues. Despite this capacity for the selective accumulation at the tumor site, clinical studies have shown the effectiveness of such I-131-Lip therapy alone to only be temporary, and early HCC recurrence was observed in many cases.…”
Section: Discussionmentioning
confidence: 99%
“…A phase I study 24 and a multi centric phase II trial 30 could not demonstrate any specific toxic effects of 131I-Lipiodol. The main limiting factor was the long patient isolation required for the purpose of radioprotection.…”
Section: Safety Of 131i-lipiodol Therapymentioning
confidence: 91%
“…Tumour response adversely correlates with tumour size. High response rates have been found in tumour nodes with diameters below 6 cm in which an absorbed dose of up to 288 Gy has been calculated 25,30,59 . However, it must be considered that a reduction in tumour mass does not necessarily correlate with improved survival 6 .…”
Section: Dosimetrymentioning
confidence: 99%